Is group and save still a necessary test in the preoperative workup for breast cancer surgery?. Issue 5 (May 2021) - Batt, Jeremy; Chambers, Alice; Mason, Jennifer; Mullan, Michelle
Introduction: Trust guidelines state that patients undergoing mastectomy have one group and save (G&S) sample preoperatively, or two for bilateral or complex mastectomy. Breast surgical patients rarely require blood transfusion, and G&S testing is costly and labour intensive. Our study assessed whether preoperative G&S testing is warranted for breast surgery patients. Methods: Retrospective review of consecutive patients undergoing mastectomies from one centre, from June 2018 to June 2019 identified 190 women. Review of electronic records for G&S tests was performed and transfusions prescribed. Discussion with laboratory personnel regarding costs of processing G&S tests. Results: Forty-six (32%) patients who underwent simple mastectomies had one G&S, eight (6%) patients had two. Twenty (45%) patients who underwent bilateral/complex mastectomy/reconstruction had one G&S and four (9%) had two. No patients required peri or postoperative blood transfusions. Seventy-eight G&S tests performed cost the trust £1, 082. Conclusion: Simple mastectomies rarely require blood transfusions. G&S tests cost £13.83 and are time consuming for the patient and laboratory. We propose that G&S tests are unnecessary for patients undergoing simple mastectomies and preoperative protocols require adjustment. Trust policy is to have 'routine G&S'; however, 124 patients did not have any G&S testing. Had the guideline been followed, this would have cost the Trust a further £1, 715.